Wakaf Uang Sebagai Instrumen Finansial Islam - Prasetyo, Sulung Jalu; Nugraha, Dhafin; Nasrullah, Muhammad Rangga; Hidayati, Amalia Nuril (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to examine the role of cash waqf in supporting sustainable economies and management strategies to optimize its impact on society. The research method used is a literature review with an interpretative approach, where data is collected from various relevant sources. The results of the study indicate that cash waqf, when managed according to Sharia principles and accompanied by innovations in its management, can provide significant social and economic benefits. Investment diversification, training for *nadzir* (waqf managers), and the role of Islamic financial institutions are crucial factors in ensuring sustainable cash waqf management. Innovations such as digital waqf platforms and social investments can also increase public participation and management effectiveness. With proper management, cash waqf can become a strategic financial instrument to support social and economic welfare while reducing social inequality in society.